Acrylamide-derived cytotoxic, anti-proliferative, and apoptotic effects on A549 cells. (May 2018) - Kacar, S; Vejselova, D; Kutlu, HM; Sahinturk, V
Background: Acrylamide is a very common compound even reaching up to our daily foods. It has been studied in a wealth of cell lines on which it proved to have various toxic effects. Among these cell lines, human lung adenocarcinoma cell line (A549) is one of that on which acrylamide's toxicity has not been studied well yet. Aim: We intended to determine the half maximal inhibitory concentration (IC50 ) dose of acrylamide and to investigate its cytotoxic, anti-proliferative and apoptotic effects on A549 cells. Methods: We determined the IC50 dose by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl-2H-tetrazolium bromide (MTT) assay. Then, the mode of cell death was evaluated by flow cytometry using Annexin-V fluorescein isothiocyanate (FITC)/propidium iodide (PI) staining. Next, we performed transmission electron microscopy (TEM) and confocal microscopy analyses for morphological alterations and apoptotic indices. Results: According to the MTT assay results, A549 cell viability decreases proportionally with increasing acrylamide concentrations and IC50 for A549 was 4.6 mM for 24 h. Annexin-V FITC/PI assay results indicated that acrylamide induces apoptosis in 64% of the A549 cells. TEM and confocal microscopy analyses showed nuclear condensations, fragmentations, cytoskeleton laceration, and membrane blebbing, which are morphological characteristics of apoptosis. Conclusion: Our research suggests that acrylamide causes cytotoxic, anti-proliferative, and apoptotic effects on A549 cells at 4.6 mM IC50 dose in 24 h.